Psychiatric manifestations in patients with dysautonomy associated with systemic lupus erythematosus (2012)
The psychiatric manifestations of three patients with systemic lupus erythematosus (SLE) and neuropathic dysautonomic processes are described. All patients had a severe form of SLE with neurological, renal, articular, pulmonary or haematological manifestations. All three have two types of psychiatric manifestations: (1) a chronic and progressive depression and (2) a complex dissociative disorder during the acute episodes of postural hypotension. A provocative test with SPECT with 99mTc-HmPAO to be done during the episode of orthostatic hypotension may contribute to clinical assessment of complex changes in cerebral regional perfusion.